PENGALAMAN KOMUNIKASI DAN KONSEP DIRI SEORANG INDIGO DI KOTA PEKANBARU - Kamaetoe, Hiro Armando; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The last few years Indigo phenomenon in Indonesia began much raised by themass-media and invited various positive and negative opinions. Some people inPekanbaru still do not know about indigo phenomenon. Some Indigo children can seethe spirits that are not caught by the sense of sight. Ability that makes an indigoreceived and considered strange refusal of the people around him. Experiences likethese can form self-concept in an indigo. This study aims to determine the experience ofcommunication, self-image, self-esteem and the factors that influence the formation ofself-concept an indigo in Pekanbaru.This study uses qualitative research with phenomenological approach to them.Subjects in this study amounted to 6 persons, consisting of 3 persons of indigodetermined through purposive sampling techniques, 1 person by significant other and 2persons by reference group. Data collected trough observation, interview, anddocumentation. Data were analyzed using an interactive model of Miles and Huberman.Technique of validating data trough the extension of partcipation and triangulation.The results of this study indicate that the communication experience an indigo inPekanbaru form a pleasant communication (positive) such as; a sense of pride and canhelp any other person with their ability, acceptance and friendship, more attention fromthe family, especially the parents, and the unpleasant communication (negative) suchas; verbal abuse. This self-image is positive even thought they are seen as negativebecause of the advantages they have no sense. Self-esteem of an indigo quite high eventhough many felt insulted but it does not affect them. Until the factors that affect selfconceptof an indigo namely the family and closest friends, which can form thecharacter of an indigo.Keywords: Experience Communications, Self-Concept, Indigo, Pekanbaru.